Clinical Presentation of Pesticides Poisoning at PMC Hospital Nawabshah - Bharat Lai, Jeeando Khan, Shaheen Mughal , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To identify different types ofpesticide poisoning by clinical features. Methods: This Cross Sectional study was conducted in the department of Medicine, Unit II, Peoples University of Medical & Health Science Nawabshah, from January 2015 to December 2015. A total of 160 patients with acute pesticide poisoning admitted were studied. Patients were quickly assessed and name and nature of pesticide was enquired. Attendants were asked to bring label or container of pesticides. At the same time patients were examined for signs and symptoms of any group of pesticide and diagnosis was made. Gastric lavage was done and antidote started. Patients having any respiratory insufficiency then they were shifted to ICU for respiratory support. Result: Out of 160 patients of pesticide poisoning, 90 were male. Their age ranged from 16-50 years. They belonged to low to middle socio economic group. According to history, signs, symptoms and label of pesticide, 112(70%) patients were exposed to organophosphorus and carbarnate, 32(200/0) were exposed to Pyrithroids, 8(5%) to Herbicides and 4(2.5%) to organochlorine compound. In 8(5%) patients cause ofpoisoning was not known. Mortality associated with pesticide poisoning was 10.5°. Conclusion: Cases of pesticide poisoning are increasing. Due to easy availability and being cheap it is preferred method of self poisoning. Label of pesticide is not always available and physician must be aware of signs and symptoms associated with different chemical groups for rapid identification and treatment.